Prevalence and factors associated with the use of benzodiazepines among teachers in Espírito Santo: a cross-sectional study - Yohan Cancilheri Mazzini; Bruna Lopes Antonucci; Guilherme Rocha Pereira; Walleri Christini Torelli Reis; Kérilin Stancine Santos Rocha; André Faro; Dyego Carlos Souza Anacleto de Araújo (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: This study analyzed the prevalence and associated factors of benzodiazepine use among teachers in municipalities of Espírito Santo, Brazil, in 2024. Methods: A cross-sectional, quantitative study conducted with teachers from the state of Espírito Santo using self-administered questionnaires. Results: Among the 453 teachers surveyed, the prevalence of benzodiazepine use was 6.8% (n=31), increasing to 21.1% (n=26) among teachers with a previous diagnosis of mental disorders (n=123). Most benzodiazepines were used daily (57.6%; n=19), 42.5% (n=14) had been used for 2-5 years, and 39.4% (n=13) reported use without antidepressant treatment. Conclusions: Severe anxiety symptoms and clinical insomnia were associated with an increased likelihood of benzodiazepine use, whereas having a partner was associated with reduced use. The prevalence of benzodiazepine use among teachers was higher than in the general population.